Phosphine Functionalized NHC Ligands and Their Cyclopentadienide Nickel(II) Complexes. Issue 17 (12th June 2018) - Trampert, Jens; Nagel, Marcel; Grimm, Tobias; Sun, Yu; Thiel, Werner R.
Abstract : By reaction of phosphine functionalized imidazolium salts with nickelocene, a series of cationic 18 VE nickel(II) half‐sandwich complexes were obtained in high yields. Herein the central nickel(II) atoms are coordinated in a chelating fashion by the N‐heterocyclic carbene (NHC) and the phosphine donor sites. The so obtained chelating ring can be opened by cyanide leading to neutral cyanidonickel(II) NHC complexes. Application of imidazolium salts functionalized with thiophosphine groups prevents the formation of chelate complexes. Instead neutral chloridonickel(II) NHC species are obtained. Abstract :